Food Safety Culture and Its Measurement in The Food Chain Company - The Contemporary Challenge of Industry Management - Anna WALASZCZYK (Communications of International Proceedings, 2021)
This study attempts to present the issue of the Food Safety Culture based on standardisation requirements and review of the reference literature. In their theoretical deliberations, the authors refer to Industry 4.0, substantiating the fact that some areas related to organisation management are not able to function without human participation. The theoretical part also includes a description of the terms Just Culture and Food Crime. The practical objective of the paper is to analyse a case study related to the Food Safety Culture implementation, on an example of a food company, as well as developing a research questionnaire for the purpose of the study, making an analysis of the study, developing a Food Safety Culture Development Plan and designing instructions for problem reporting by the employees.
Keywords: Food Safety Culture; Just Culture; Food Crime; management